The rise of guesthouse tourism in the Greater Caucasus and the effects of the covid pandemic. The example of Lagodekhi town and its Protected Area, Georgia - Schmid, Leonie Greta; Gugushvili, Temur; Kohler, Thomas (ERDKUNDE, 2022)
In Georgia, tourism has become a key sector of the economy, especially since the country opened up for private investment after independence in 1991. Guesthouses, the focus of this paper, present a typical example of such private investment. In dealing with this sector, we adopt a synoptic view, and look into development over time, services offered, motives for hosting guests, outcomes, and the effects of the COVID pandemic. Geographically, our focus is on the town of Lagodekhi and its Protected Area (PA) on the foot slope of the Greater Caucasus. Our methods included a review of literature, followed by a questionnaire survey in 2018 among all 23 guesthouses in the town, covering qualitative as well as quantitative aspects of the sector. To follow up on the effects of the pandemic, which reached the area in 2020, we did a re-survey among all houses in June 2021. The results show that all guesthouses are owner-occupied and family-run, with women taking the lead, following traditional gendered labour division. The owners see themselves as paid service providers but also as hosts, who offer insights into local culture free of charge based on traditional hospitality. We posit that this dual role is a unique selling proposition, distinguishing the sector from mass tourism, and presenting an ideal complement to the nature-based attractions of the PA. The COVID pandemic led to an almost total collapse of this sector, especially relating to foreign guests, by far the most numerous visitor group. But the guesthouses remain positive about the future and continue to invest in their houses. To conclude our paper, we present ideas relating to the future of guesthouse tourism in the study area, based on experience before and with the pandemic.